2013
DOI: 10.1073/pnas.1212593110
|View full text |Cite
|
Sign up to set email alerts
|

Economic repercussions of fisheries-induced evolution

Abstract: Fish stocks experiencing high fishing mortality show a tendency to mature earlier and at a smaller size, which may have a genetic component and therefore long-lasting economic and biological effects. To date, the economic effects of such ecoevolutionary dynamics have not been empirically investigated. Using 70 y of data, we develop a bioeconomic model for Northeast Arctic cod to compare the economic yield in a model in which life-history traits can vary only through phenotypic plasticity with a model in which,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 32 publications
4
83
1
1
Order By: Relevance
“…However, the sign of the selection differentials on reproductive investment remained identical whether density-632 dependence was acting on growth or not. Moreover, the key predictions emerging from our stylized model were roughly similar to the predictions of more complex eco-genetic 634 models in terms of the expected evolution of fast life histories under most situations in fisheries (Eikeset et al 2013;Dunlop et al 2015b). Nevertheless, it is clear that our 636 work shall be extended and replicated with other model frameworks to analysis its stability.…”
Section: Model Limitationsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the sign of the selection differentials on reproductive investment remained identical whether density-632 dependence was acting on growth or not. Moreover, the key predictions emerging from our stylized model were roughly similar to the predictions of more complex eco-genetic 634 models in terms of the expected evolution of fast life histories under most situations in fisheries (Eikeset et al 2013;Dunlop et al 2015b). Nevertheless, it is clear that our 636 work shall be extended and replicated with other model frameworks to analysis its stability.…”
Section: Model Limitationsmentioning
confidence: 84%
“…Fast life-histories can be characterized by fast juvenile growth, young age and small size at maturation and high reproductive investment, which reduce post-80 maturation growth rate and increase natural mortality. From a management 5 perspective, it is important to understand the population dynamical and social and 82 economic consequences of fisheries-induced evolution, to, if possible, design management tools that minimize undesired evolutionary effects on outcomes valued by 84 humans, such as yield, recovery or the catch prospects of exceptionally large fishes (Matsumura et al 2011;Eikeset et al 2013;Zimmermann & Jørgensen 2017). 86…”
mentioning
confidence: 99%
“…Furthermore, selective fishing pressure based on size may lead to the appearance of small adult individuals, as observed in Turks and Caicos Islands (Clerveaux, Danylchuk, & Clerveaux, 2005) and Berry Island, Bahamas (Stoner et al, 2012b). Fish stocks experiencing high fishing mortality show a tendency to mature earlier and at a smaller size (Eikeset, Richter, Dunlop, Dieckmann, & Stenseth, 2013), which may also reduce fecundity (Marshall, Needle, Yaragina, Ajiad, & Gusev, 2004). Large queen conch have higher reproductive potential than smaller individuals (Stoner et al, 2012a), so it can be concluded that fishing regulations based on shell length may also decrease the reproductive potential of a population through size selection.…”
Section: Discussionmentioning
confidence: 99%
“…The evolutionary effects of fishing, particularly on age and size at maturation, have been studied in the northern cod stocks of the Baltic Sea, Norwegian Sea and Icelandic shelf [72][73][74], and also in the Norwegian Spring-spawning herring stocks [75]. Harvest-induced evolution can affect the fishery's yield and therefore have economic repercussions for society as shown for the Barents Sea cod [76]. Perhaps counter intuitively evolutionary change may be mostly beneficial for the stock productivity and economic yield of the stock, as long as the fishing mortality is low because in this case, the adaptive capacity of the fish stock is maintained [76].…”
Section: Ecosystem Dynamicsmentioning
confidence: 99%
“…Harvest-induced evolution can affect the fishery's yield and therefore have economic repercussions for society as shown for the Barents Sea cod [76]. Perhaps counter intuitively evolutionary change may be mostly beneficial for the stock productivity and economic yield of the stock, as long as the fishing mortality is low because in this case, the adaptive capacity of the fish stock is maintained [76]. However, if fishing mortality is particularly high, productivity is actually lower if the fishery is catching all fish above a certain minimum size, which is currently the case for the Barents Sea cod.…”
Section: Ecosystem Dynamicsmentioning
confidence: 99%